The Effect of Online Queue Implementation and Service Quality on Patient Satisfaction at Kendangsari Mother and Child Hospital Surabaya - Tri Hedianto; Farida Yuliaty; Ayu Laili Rahmiati; Kosasih; Vip Paramarta (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Digital transformation in healthcare, particularly through online queue systems, has become a vital instrument for improving operational efficiency and patient comfort in the post-pandemic era. This study aims to analyze the effect of online queue implementation (X₁) and service quality (X₂) based on SERVQUAL dimensions on patient satisfaction (Y) at RSIA Kendangsari Surabaya. A quantitative descriptive approach was applied using multiple linear regression analysis on 121 outpatient respondents who utilized the online queue system. The results show that online queue implementation does not have a significant partial effect on patient satisfaction (t=0.971, sig.=0.333), as it is perceived as a standard facility (hygiene factor). Service quality, however, has a significant positive partial effect (t=5.952, sig.=0.000). Simultaneously, both variables significantly influence patient satisfaction (F=29.672, sig.=0.000) with a coefficient of determination of 33.46%. Management is advised to prioritize service quality improvements, especially staff empathy (Empathy) and responsiveness, while continuously optimizing the technical features of the online queue system.